The Symbolism of Faith and Identity: A Phenomenological Study of Malay Traditional Houses in Bengkalis, Indonesia (International Journal of World Civilizations and Philosophical Studies, 2026)
This study examines the symbolic link among faith, identity, and architecture through a phenomenological and semiotic analysis of traditional Malay houses in Bengkalis, Indonesia. Moving beyond typological and structural study, the research examines how architectural elements-such as spatial orientation, elevation, ornamentation, and material choices-reflect the Islamic worldview and Malay moral philosophy. Using qualitative document analysis and visual interpretation, the study examines the traditional house as a lived space that demonstrates how belief and culture converge in its built form. Results indicate that the Malay house functions as a living cosmology, in which architecture expresses tawhid (divine unity), adab (ethical propriety), and ukhuwah (community harmony). The Qiblah direction symbolizes submission to divine order, while the raised platform (rumah panggung) stands for transcendence and purity. Carvings and ornaments (ukiran) function as visual dhikr, reminding of God through beauty and symmetry. Natural materials reflect an ecological awareness grounded in Islamic ethics of balance (tawazun). By combining phenomenological experience with semiotic interpretation, the study discusses Islamic aesthetics and sustainable cultural heritage. It concludes that the traditional Malay house is both a theological and architectural symbol-a dwelling that teaches and reminds us that to build is to believe, and to dwell is to remember.